2011
DOI: 10.1124/jpet.111.184630
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Potentiation of the Antitumoral Activities of FK866, an Inhibitor of Nicotinamide Phosphoribosyltransferase, and Etoposide or Cisplatin in Neuroblastoma Cells

Abstract: NAD is an essential coenzyme involved in numerous metabolic pathways. Its principal role is in redox reactions, and as such it is not heavily "consumed" by cells. Yet a number of signaling pathways that bring about its consumption have recently emerged. This has brought about the hypothesis that the enzymes that lead to its biosynthesis may be targets for anticancer therapy. In particular, inhibition of the enzyme nicotinamide phosphoribosyl transferase has been shown to be an effective treatment in a number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…Because a previous study linked cell death induced by FK866 combined with cisplatin/etoposide to apoptosis in neuroblastoma cells, 12 we next examined whether FK866 added to bortezomib also triggered apoptosis in MM cells. Indeed, we observed that combining low doses of these drugs markedly increased proteolytic cleavage of caspase-3, caspase-8, caspase-9, and PARP in both bortezomib-sensitive and -resistant MM cell lines ( Figure 3A).…”
Section: Targeting Nampt and Proteasome Activity Triggers Synergisticmentioning
confidence: 99%
See 2 more Smart Citations
“…Because a previous study linked cell death induced by FK866 combined with cisplatin/etoposide to apoptosis in neuroblastoma cells, 12 we next examined whether FK866 added to bortezomib also triggered apoptosis in MM cells. Indeed, we observed that combining low doses of these drugs markedly increased proteolytic cleavage of caspase-3, caspase-8, caspase-9, and PARP in both bortezomib-sensitive and -resistant MM cell lines ( Figure 3A).…”
Section: Targeting Nampt and Proteasome Activity Triggers Synergisticmentioning
confidence: 99%
“…Remarkably, the combination of FK866 plus bortezomib dramatically reduced intracellular NAD 1 to undetectable levels in all MM cells analyzed, enhancing the metabolic consequences of FK866 treatment alone ( Figure 6A). Because intracellular NAD 1 and adenosine triphosphate (ATP) levels, whose depletion follows NAD 1 shortage, 12,27 share the capacity to affect proteasome enzymatic activity, we next turned our attention to a possible synergism at this level.…”
Section: Combined Fk866 and Bortezomib Inhibits The Ups And Nf-kb Patmentioning
confidence: 99%
See 1 more Smart Citation
“…FK866 reduces intracellular NAD content, resulting in selective cancer cell death in solid tumors (22,(25)(26)(27), and emerging evidence suggests that it is also active in blood cancers (28)(29)(30)(31)(32)(33). FK866 has been demonstrated to be effective in blood cancer cell lines, where it leads to ATP reduction and delayed induction of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…GMX1777 is a soluble prodrug of GMX used for in vivo studies (5,6). NAMPT inhibitors, including GMX1778 (GMX) and FK866, have shown preclinical activity alone and in combination with several therapeutic DNA-damaging agents, but the mechanism of synergy has not been clearly elucidated (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%